The sphere of participatory in the new spectator paradigm: Andrés Lima, Àlex Rigola, Alfredo Sanzol y Pablo Remón - Rodriguez Alonso, Mariángeles (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The spectator paradigm has been modulated from positions that redefine it as an accomplice of the game and an active participant in the theatrical party to those that vindicate and reformulate his ritual presence. The present approach thus explores some of the contemporary Spanish directors’ conception of the viewer (we will focus on Andrés Lima, Álex Rigola, Alfredo Sanzol y Pablo Remón), with the intention to offer some reflections on the different roles, attitudes or directions that the latter adopts on the Spanish stage today. contemporary stage creators, from the intersection of the concepts of theatricality and performativity revealed by their poetics, put the figure of the viewer in the spotlight and test new formulas for more intense and effective communication.